2017
DOI: 10.1016/j.jcmgh.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gastric Metaplasia, Dysplasia, and Neoplasia by Bone Morphogenetic Protein Signaling

Abstract: The bone morphogenetic proteins, (BMP)s are regulatory peptides that have significant effects on the growth and differentiation of gastrointestinal tissues. In addition, the BMPs have been shown to exert anti-inflammatory actions in the gut and to negatively regulate the growth of gastric neoplasms. The role of BMP signaling in the regulation of gastric metaplasia, dysplasia and neoplasia has been poorly characterized. Transgenic expression in the mouse stomach of the BMP inhibitor noggin leads to decreased pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 79 publications
(111 reference statements)
0
28
0
Order By: Relevance
“…The actions of these proteins can be blocked by secreted inhibitory molecules, such as noggin, gremlin, and chordin, which are expressed in vivo to modulate the actions of the BMPs. 24 , 25 It has been shown that loss of BMP signaling in the stomach leads to perturbations of the normal homeostatic mechanisms of the gastric mucosa, leading to the development of metaplasia, dysplasia, and neoplasia. 25 , 26 , 27 In support of these observations studies have shown that BMP receptors such as BMPR1A and the BMP signal transducing proteins Smad1, 5, and 8 are widely expressed in the glandular stomach.…”
mentioning
confidence: 99%
“…The actions of these proteins can be blocked by secreted inhibitory molecules, such as noggin, gremlin, and chordin, which are expressed in vivo to modulate the actions of the BMPs. 24 , 25 It has been shown that loss of BMP signaling in the stomach leads to perturbations of the normal homeostatic mechanisms of the gastric mucosa, leading to the development of metaplasia, dysplasia, and neoplasia. 25 , 26 , 27 In support of these observations studies have shown that BMP receptors such as BMPR1A and the BMP signal transducing proteins Smad1, 5, and 8 are widely expressed in the glandular stomach.…”
mentioning
confidence: 99%
“…Some of the major regulators of gastric stem cell proliferation and differentiation include sonic hedgehog (Shh) and bone morphogenetic proteins (BMPs) signaling pathways. These have been found to exert important effects on gastrointestinal development and differentiation (Lees et al, 2005;Todisco, 2017). In the human stomach, Shh expression is restricted to the parietal cells and the glandular portion (van den Brink et al, 2001), where it controls epithelial cell proliferation and serves as a polarizing signal for fundic gland differentiation Lgr5 leucine-rich repeat-containing G-protein coupled receptor 5, TFF2 trefoil factor 2, Sox2 sex-determining region Y box protein 2, CCK2R cholecystokinin type-B receptor, Lrig1 leucine-rich repeats and immunoglobulin-like domains 1, AQP5 aquaporin 5, Ach acetylcholine, EGF epidermal growth factor, FGF10 fibroblast growth factor 10, BMPs bone morphogenetic proteins, Shh sonic hedgehog.…”
Section: Gastric Stem Cells and Their Nichementioning
confidence: 99%
“…Mechanistically, HH produced by epithelial cells induces the expression of COUP-TFII in mesenchymal cells to block the excessive expansion of circular smooth muscle cells and enteric neurons. At the same time COUP-TFII indirectly inhibits the epithelium proliferation; the mediator of this negative feedback loop is probably the secreted factor BMP-4, as demonstrated by the fact that the reduction of BMP signaling increases epithelial proliferation [154,155].…”
Section: Infertility and Alterations Of Mesenchymal Commitmentmentioning
confidence: 99%